2018
DOI: 10.25165/j.ijabe.20181104.2729
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental investigation of laminar flow mixing system in a pitched-blade turbine stirred tank

Abstract: The flow distribution and mixing performance of the laminar flow in the PBT impeller-stirred tank were investigated in this study. The variation along with mixing time of the flow distribution and concentration at the selected positions was visualized by means of the CFD and experiment methods. The CFD simulations results had a good agreement with the experimental results. In order to minish the Segregated Regions, the PBT impeller was optimally designed by means of orthogonal factorial experiment with selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Haider and Levenspiel (HL) [26] studied the drag coefficient and terminal velocity of spherical and non-spherical particles shaped as isometric like cube octahedrons, octahedrons, cubes, tetrahedrons and thin free-falling disks. They derived the equation of drag coefficient related to the particle Reynolds number and sphericity , see Equation (8). Hölzer and Sommerfeld (HS) [30] proposed a drag model for nonspherical particles (Equation ( 9)) based on the existing drag models.…”
Section: R F Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Haider and Levenspiel (HL) [26] studied the drag coefficient and terminal velocity of spherical and non-spherical particles shaped as isometric like cube octahedrons, octahedrons, cubes, tetrahedrons and thin free-falling disks. They derived the equation of drag coefficient related to the particle Reynolds number and sphericity , see Equation (8). Hölzer and Sommerfeld (HS) [30] proposed a drag model for nonspherical particles (Equation ( 9)) based on the existing drag models.…”
Section: R F Pmentioning
confidence: 99%
“…Whether it is gas mixing [7] or mechanical mixing [8] , the appropriate mixing of biomass particles needs to be solved to improve anaerobic digestion [9] . Computational fluid dynamics (CFD) simulation technology is a promising technique to study the mixing process between particles and fermentation fluids to optimize the agitator design [10][11][12] by visualizing the mixing process with simulation.…”
Section: Introductionmentioning
confidence: 99%
“…When the studies on these parameters are examined, it has been seen that the undesired vortexes in the tank can be prevented by the baffles added to the inner walls of the tank (Rezend, 1996;Missen et al, 1999). Cui et al experimentally and numerically investigated the mixing process for laminar flow in pitched-blade turbine stirred tanks (Cui et al, 2018). They concluded that the impeller diameter was the parameter that most influenced the mixing time.…”
Section: Introductionmentioning
confidence: 99%